In vitro interaction of macrocyclic photosensitizers with intact mitochondria: a spectroscopic study - Synytsya, Alla; Kral, Vladimir; Synytsya, Andriy; Volka, Karel; Sessler, Jonathan L (Biochimica et biophysica acta, 2003)
Six water-soluble macrocyclic photosensitizers, the members of two groups of expanded porphyrins (metallotexaphyrins and free-base sapphyrins) containing hydrophilic substituents and meso-tetra(4-sulfonatophenyl)-porphyrin, were tested by UV-Vis absorption and resonance Raman spectroscopy in the in vitro binding experiments with intact mitochondria isolated from swine liver. Studied macrocycles showed markedly different affinity to mitochondria. The highest uptake was observed for sapphyrin-sugar conjugate and metallotexaphyrins. Sapphyrin-polyamine conjugates exhibit something less affinity to mitochondria, while the porphyrin of anionic character showed very low mitochondrial uptake. Obtained spectroscopic results confirm that the binding process altered the self-aggregation degree of expanded porphyrins.
Keywords: algoritmy; Spectrum Analysis, Raman; Algorithms; porfyriny; Porphyrins; Mitochondria, Liver; Spectrophotometry; Photosensitizing Agents; fotosenzibilizující látky; jaterní mitochondrie; fotochemoterapie; Swine; zvířata; Photochemotherapy; spektrofotometrie; molekulární struktura; prasata; Ramanova spektroskopie; Molecular Structure; Animals